Pengkajian Administrasi Dan Farmasetis Resep Anak di Apotek G Madiun - Rita Septiana; Khotimatul Khusna; Ayu Palupi (Universitas PGRI Madiun, 2021)
Prescription assessment is one of pharmaceutical service activities that aims reduce medication errors and improve patient safety. This study aims to see administration and pharmaceuticals completeness on children's prescriptions at Pharmacy G Madiun city. This research is observational descriptive, sample is childrens prescription who received at G pharmacy period juni-agustus 2019. In this study, prescriptions studied was 300 recipes. This research shows: completeness doctors name 100%, doctors address 100%, sign R/ 100%, drugs name 100%, drugs strength 100%, drugs amount 100%, drugs rule used 100%, signature or doctors initial 99,6%, doctors telephone number 99,3%, patients name 99%, prescriptions date 97%, doctors SIP 81,6%, patients age 62%, patients address 28,3%, patients weight 2,6%, patients height 0,67% and patients gender 0%. Based on pharmaceutical assessment showed suitability of dosage form and patients 100%, drugs stability 100%, how to drugs use 100%, prescription incompatibility 0%.